Nucleation of filaments of the TGBA phase in free-standing films. Issue 2 (26th January 2018) - Lejček, Lubor; Novotná, Vladimíra; Glogarová, Milada
ABSTRACT: A model of filament nucleation in the twist grain boundary A (TGBA) phase in free-standing smectic films is proposed. It is based on a concept of finite blocks of parallel smectic layers forming a helical structure in the interior of a film. In our model, the blocks resemble twin-like domains in smectic-A liquid crystal. The blocks are mediated to surrounding smectic layers in film either continuously (coherent twin boundary) or discontinuously via dislocation loops wrapping up blocks. Edge components of dislocation loops form incoherent twin boundary. Screw components forming twist grain boundary connect neighbour blocks among themselves. Nucleation of TGBA filament in a film is treated using a simplified model based on isotropic smectic-A elastic theory. Discussion showed that filaments can be nucleated just below the transition temperature from the isotropic to the TGBA phase under slow temperature decrease. The nucleation of dislocation loops is possible due to low compression modulus of material which can be expected just below the transition temperature. Graphical Abstract: